2004
DOI: 10.1677/erc.1.00799
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I receptor signalling and acquired resistance to gefitinib (ZD1839; Iressa) in human breast and prostate cancer cells

Abstract: De novo and acquired resistance to the anti-tumour drug gefitinib (ZD1839; Iressa), a specific epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) has been reported. We have determined whether signalling through the IGF-I receptor (IGF-1R) pathway plays a role in the gefitinib-acquired resistance phenotype. Continuous exposure of EGFR-positive MCF-7-derived tamoxifen resistant breast cancer cells (TAM-R) to 1 mM gefitinib resulted in a sustained growth inhibition (90%) for 4 months before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
190
2
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(211 citation statements)
references
References 46 publications
14
190
2
5
Order By: Relevance
“…However, a very important and general drawback with cancer drugs, also concerning targeting with small molecules and antibodies (Chen et al, 2004;Jones et al, 2004;Nagata et al, 2004;Peggs, 2004), is the generation of drug resistance (Longley and Johnston, 2005). For this reason, we found it highly relevant to investigate whether resistance to PPP may occur after long-term treatment in a cellular context, as well as to characterize the obtained resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, a very important and general drawback with cancer drugs, also concerning targeting with small molecules and antibodies (Chen et al, 2004;Jones et al, 2004;Nagata et al, 2004;Peggs, 2004), is the generation of drug resistance (Longley and Johnston, 2005). For this reason, we found it highly relevant to investigate whether resistance to PPP may occur after long-term treatment in a cellular context, as well as to characterize the obtained resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The interplay of these two receptor pathways may lead to resistance by the tumor to inhibition of one receptor via compensatory upregulation/activation of the reciprocal receptor, and dual inhibition of EGFR and IGF-1R has been shown to improve anti-tumor activity and overcome resistance to therapy against a single receptor in preclinical models. [17][18][19][20][21][22][23][24] Moreover, co-expression of EGFR and IGF-1R has been reported in many human tumors, including lung, colorectal and pancreatic carcinoma, [25][26][27] supporting dual targeting of these two receptors in these indications. Clinically, EGFR inhibitors are known to be efficacious in only a subpopulation of cancer patients, and intense research for molecular predictors of clinical outcomes to EGFR targeted therapies has identified K-Ras mutation as a predictive biomarker of resistance to EGFR mAbs treatment in colorectal cancer and EGFR gene mutation or high copy number as strong indicators of response to EGFR TKIs in lung cancer.…”
Section: Generation Of Bispecific Antibody Directed Against Egfr and mentioning
confidence: 99%
“…This activates the kinase activity of IGF-IR, and triggers downstream signaling via the PI3K/Akt and Ras/MAPK pathways, resulting in increased cell survival and cell proliferation (16,17). Elevated IGF-IR is found in many tumor malignancies, including breast, prostate, and lung cancers (18,19). In addition, overexpression of IGF-IR has been associated with disease progression and cancer metastasis (20,21).…”
Section: Introductionmentioning
confidence: 99%